NOVATION, IMPLEMENTATION OF NOVATION, INNOVATION – CONCEPTUAL SEMANTIC IN INNOVATION SCIENCE - Yaloveha, I.; Zub, S. (Physical and Mathematical Education, 2021)
Formulation of the problem. Training future specialists for innovation activities, which is currently one of the main purpose of education, requires first of all the obligatory mastery of the conceptual apparatus of innovation science, in which there is still no clearly defined terminology. Today there are a huge number of definitions of the concept of "innovation" depending on the scope of the results of innovation activities. Most often, along with the concept of «innovation» use such related concepts as «discovery», «invention», «novation», «implementation of novation» that often replace «innovation», considering them synonyms. «Novation», «implementation of novation», «innovation» are widely used in Ukrainian and Russian sources, while in English sources the term «innovation» is often general and includes all three concepts. The aim of the article is a semantic analysis of the basic terms of innovation science, analysis of differences in similar concepts, and, as a consequence, the formulation of common to different industries definitions of «novation», «implementation of novation», «innovation».Materials and methods. The following methods were used in the study: analysis and synthesis of the content of philosophical, cultural, linguistic, economic, technical, psychological and pedagogical, historical scientific and methodological research on the problem of forming the conceptual apparatus of innovation; comparative-historical, retrospective methods; structural and logical analysis.Results. The conducted etymological analysis of the words «discovery», «invention», «novation», «innovation» (in Ukrainian, Russian, English) provided an opportunity to understand the inherent presence of these words at the beginning of their appearance. A separate study of the origin of the word pair «novation-innovation» based on the analysis of similar pairs of Latin words provided an explanation of the semantic load of the Latin prefix «in-» to the original word. The analysis of Ukrainian, Russian and English languages scientific papers on innovation science revealed a significant difference in the use of basic terms. Semantic analysis of the concepts «novation», «implementation of novation», «innovation», determination of the peculiarities of the use of these concepts in philosophy, culturology and economics provided opportunities to distinguish coincidences in semantic load and common parts of formulations in their definitions. Based on the study proposed use of the terms «novation», «implementation of novation», «innovation» in innovation science as the separate categories, and formulated general definitions of these concepts for any application.Conclusions. The study conducted revealed the existence of a large number of differences, inaccuracies and contradictions in the definitions, inconsistencies in terminology in different languages. The formulations of general definitions of concepts corresponding to the stages of the innovation process proposed in the work provide an opportunity to further develop an ontological model in innovation science, determine its structure and relationships between objects, which is also important for presenting data in algorithmic machine-interpreted form. The formation of the conceptual apparatus, clear terminology, formulation of common for different industries definitions of the basic concepts is a necessary stage in the formation and further development of innovation.
Keywords: innovation science; conceptual semantic; novation; implementation of novation; innovation; discovery; invention